Service and pricing strategies with competition and cooperation in a dual-channel supply chain with demand disruption. (December 2019) - Pi, Zhenyang; Fang, Weiguo; Zhang, Baofeng
Highlights: We mathematically model the price and service competitions with demand disruptions. The optimal strategies in retailer competition and cooperation models are derived. Retailer cooperation benefits retailers but harms the manufacturer and the system. Each retailer benefits from other channels' demand disruptions. The manufacture and system are worse-off caused by any channel's demand disruption. Abstract: We study the pricing and service strategies with retailers' competition and cooperation in a dual-channel supply chain system consisting of one manufacturer and two retailers, in which the manufacturer sells a single product through an online direct channel and two retail channels. Providing the product with value-added service, each retailer, in the presence of price and service competitions, can choose to cooperate or not. Considering each channel's demand disruption, where the disrupted demand switches to other channels, and using game theory and two-stage optimization method, we derive the Stackelberg-Nash equilibrium in retailer cooperation (RC) model and retailer independence (RI) model, respectively. We conduct numerical experiments and find that the retailers' cooperation enhances each retailer's performance, but surprisingly reduces the profits of the manufacturer and the whole system. In both models, one retailer benefits from the demand disruption of other channels, whereas the manufacturer and the whole system are always worse-off in the presence of demand disruption from any channel, and better-off when the disrupted demand of one channel switches more to other channels.